Exploration of the Decline of Students' Interest in Studying in Higher Education: Psychological and Sociological Perspectives - Fauzan, Fauzan; Ubaidillah, Ubaidillah (Journal of Science and Education (JSE), 2025)
The decline in students' interest in studying in higher education is a crucial issue in higher education. This study aims to identify psychological and sociological factors that influence this phenomenon and examine its implications for the sustainability of education. Using a qualitative approach and in-depth interview method, this study found that academic pressure, lack of intrinsic motivation, and achievement anxiety are the main psychological factors. Meanwhile, social norms, family support, and social media influence are significant sociological factors. Strategic recommendations include the provision of counseling services, family involvement, and self-development programs based on labor market needs. This study provides theoretical and practical contributions to the management of higher education.